Metode Pendidikan Islam Dalam Perspektif Filsafat Pendidikan Islam - Dayu Feri Apriliansah; Faridi Faridi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Education is important for the progress of a nation, therefore education must have the right methods so that education can run smoothly and achieve its goals. Educational methods must be appropriate to local environmental, social and cultural conditions, efforts to carry out appropriate education can be applied, so that educational goals can be achieved. As a teacher, you must be able to master educational methods, therefore the methods used by a teacher must be appropriate to the class conditions at hand. The importance of the method applied is one of the success factors in efforts to achieve educational goals. Islamic philosophy has its own perspective in assessing education, success in mastering various kinds of knowledge alone is not enough to be a factor in educational success. The education expected through Islamic education methods must reflect a form of step in perfecting noble morals. Scientific intelligence cannot yet be used as a benchmark for educational success, therefore educational methods must be in accordance with behavior that reflects the Islamic values ​​contained therein, so that the knowledge obtained can be balanced with Islamic character and behavior which prioritizes the moral values ​​contained therein.